Regression analysis of strength coach salary and its effect on on-field performance and academic progress rate in division 1 football - Castiglione, Joseph Jr (My University, 2021)
Finding an edge to increase the likelihood of success of their student athletes’ is always at the forefront of college athletics administrators. Previous studies have investigated the relationship of coaching salaries and on field performance in college football. Athletic budgets, talent level, head coaching salary But none have looked at the relationship of the investment of strength and conditioning coach and how it relates to academic and on field performance. Many medical studies have shown that exercising has increased cognitive performance, but none have made the connection of how this plays a role into the success of our elite college athletes. This study looks into the relationship between not only strength coach salary but other contributing factors of State population, athletic budgets, conference affiliation, head football coach salary, and talent were all used as control variables. Performing a ordinary least squares regression analysis on averaged data from years 2016-2018, with a total of 267 observable groupings. An OLS Regression will also be performed on the same year but the average of the variables for each school. Initial correlational analysis showed promise of salary with on field performance. Talent was the strongest indicator of a higher winning percentage. While Strength and conditioning coach salary was not positively correlated with Academic Progress Rate, which is an annual four year average combined of GPA and graduation track of current athletes. While the relationship was not strong showing that funding a SCC does translate to on field performance will be key for this industry.
Keywords: Strength; Division 1 Football Strength; Academics in Division 1 Football; Winning Percentage and Salary